The effect of warm-up on peak impact force of the rear hand strike in full-contact combat sports - Trebicky, V.; Rudolf, J.; Pavelka, R. (Sports Biomechanics, 2024)
Warming up is a generally accepted practice that leads to improved performance and reduces the risk of injury in a wide range of sports. However, the evidence about the influence of warm-up in combat sports is limited and, specifically, little is known about the impact which delays between a warm-up and the start of a match may have on fighters` performance. This study investigates the influence of warm-up and cool-down on one of significant performance predictors in full-contact combat sports, the peak force of a rear hand strike, in a sample of 31 athletes.Peak impact force was measured before, after, and at two time points after a standardized warm-up routine; skin temperature and heart rate were also monitored. Warm-up and cool-down periods were substantial predictors of body temperature and heart rate, but we observed no effect of the warm-up routine on strike impact force. Strike impact force remained unaffected even after the cool-down intervals.Strike impact force does not seem to respond to physiological changes elicited by a warm-up. This measure is partly related only to fighters` physical characteristics, namely the body weight. Athletes and trainers could thus concentrate on other aspects of successful performance during warm-up routines.